Horizontal application of fundamental rights : An overview of Constitutional provisions and judicial interpretation (International Journal of Food and Nutritional Sciences, 2024)
Fundamental rights are the Magna Carta of the Indian Constitution. A research paper would examine how Indian courts have interpreted the Constitution to enforce fundamental rights not just against the state ("vertical application"), but also between private individuals or entities ("horizontal application"), analyzing key legal provisions and landmark cases that have shaped this doctrine in India.